THE INFLUENCE OF THE SPORTS TRAINING ON THE DEVELOPMENT OF SOME SPECIFIC PHYSICAL ABILITIES OF THE FEMALE HANDBALL PLAYERS - Dobrislav Vujović; Jovica Petković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The sustained and systematic training processes related to the handball have various influences on creating those anthropological characteristics that can be influenced on the basis of exogenesis. A well organized, longer training process is a very important factor that can significantly influence on the quality and quantity of those characteristics of the players that are not being inborn. The objective of the paper is to show the influence of the programmed triennial handball training on the changing of the physical abilities of the female handball players of the Montenegrin national team.